Promosi Kualitas Kebugaran Jasmani Anak Disabilitas Intelektual dengan Pendekatan Edusehat Bagi Guru MGMP PJOK Adaptif - Sumaryanti Sumaryanti; Atikah Rahayu; Vistor Syapri Maulana (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The implementation of the Clean and Healthy Lifestyle Behavior (PHBS) program globally, nationally, including in Yogyakarta, is still low and even declining among school-age children, including children with disabilities. This condition is known from the trend of the last 10 years of PHBS implementation from 56.5% to 55.6%. The implementation of PHBS is important, because it affects the quality of children's health, especially children with intellectual disabilities, one of the groups (population at risk) experiencing pain due to the non-implementation of PHBS. The limitations of people with intellectual disabilities, the involvement of all family members, teachers/trainers is very necessary to accompany PHBS implementation activities. For the successful implementation of PHBS for children with intellectual disabilities in schools, it is necessary to bridge the gap between instructors/trainers and teachers. Considering that not all teachers, trainers, and instructors are familiar with the PHBS program, and usually the PHBS program is often socialized among households, health institutions/community health centers and non-inclusive schools. The purpose of Community Service (PkM) is to improve the knowledge and skills of adaptive MGMP PJOK teachers in the Edusehat program (Clean and Healthy Lifestyle Behavior Education). The Community Service Program (PKM) activity plan is divided into three stages: Preparation, Implementation, and Evaluation. In the Preparation stage, the community service team collaboratively develops an edusehat program for all practitioners, both teachers and trainers, in implementing the program. In the Implementation stage, the program includes the implementation of edusehat program activities. In the Evaluation stage, the community service team evaluates a series of community service activities. The evaluation results indicate an increase in the level of knowledge and skills of PHBS indicators before and after Edusehat was provided. Considering the significant benefits of PkM for teachers and their students, MGMP recommends that these activities continue to be held and collaborated with other activities such as competitions and festivals for children with disabilities that are more broadly related to the implementation of PHBS.